An experience-based learning framework: Activities for the initial development of sustainability competencies. Issue 6 (7th November 2016) - Caniglia, Guido; John, Beatrice; Kohler, Martin; Bellina, Leonie; Wiek, Arnim; Rojas, Christopher; Laubichler, Manfred D.; Lang, Daniel
Abstract : Purpose: This paper aims to present an experience-based learning framework that provides a bottom-up, student-centered entrance point for the development of systems thinking, normative and collaborative competencies in sustainability. Design/methodology/approach: The framework combines mental mapping with exploratory walking. It interweaves mapping and walking activities with methodological and theoretical inputs as well as with reflections and discussions. The framework aligns experiential activities, i.e. mental mapping and walking, with learning objectives, i.e. novice-level sustainability competencies. The authors applied the framework for student activities in Phoenix/Tempe and Hamburg/Lüneburg as part of The Global Classroom, a project between Arizona State University in the USA and Leuphana University of Lüneburg in Germany. Findings: The application of the experience-based learning framework demonstrates how students started developing systems thinking (e.g. understanding urban systems as functional entities and across different domains), normative (e.g. using different sustainability principles) and collaborative (e.g. learning across disciplinary, social and cultural differences) competencies in sustainability. Originality/value: The experience-based learning framework contributes to the development of curricular activities for the initial development of sustainability competencies in introductory-level courses. It enables students from different disciplinary, social and cultural backgrounds, e.g. in international education, to collaboratively start developing such competencies. The framework can be adapted to different educational contexts.